Regulation of Changes in Proteins and Enzymes Associated with Active Defence against Virus Infection - Van Loon L.C.
Plant viruses possess only a limited amount of genetic information. Apart from the gene(s)for coat protein and one or two large polypeptides presumed to be involved in virus replication, information for only one to a few specific disease-inducing proteins can be present. This conclusion is reinforced by the existence of viroids, the smallest pathogens known, which contain as few as 359 nucleotides. No specific viral protein(s)involved in pathogenesis have as yet been identified, neither by in vitro translation of viral nucleic acids in cell-free protein-synthesizing systems, nor by in vivo analysis of changes in protein profiles of host plants upon infection. Contrary to metabolic changes after infection with fungi or bacteria, those resulting from virus infection appear to be solely reactions of the host plant and connected primarily with the type and severity of the symptoms produced: essentially all of these changes are also found after infection with fungi and bacteria that induce similar symptoms. Apparently, the ability of the host plant to react in the particular way it does, is present in a "cryptic" form all the time, but is evoked only by the triggering action of the infecting virus. The genetic information underlying symptom expression may never be expressed during normal plant development, or, if it is, upon virus infection it is expressed in an untimely or uncoordinated way, no longer subject to common regulatory controls, thus giving rise to the particular symptoms characteristic of the disease.
Keywords: STARCH; PHENOL; ASPIRIN; RESPIRATION; PHENYL